Photo-Electrochemical Performance of Interpenetration-Structured Heterojunction by Overlapping CuO and ZnO Nanorod Arrays. Issue 6 (4th June 2021) - Wu, Fan; Pathak, Rajesh; Zhang, Tiansheng; Xu, Haibing; Tong, Yanhua; Jian, Ronghua; Qiao, Qiquan (Quinn)
Abstract : A facile design of interpenetration-structured p–n heterojunction device was fabricated by overlapping p-CuO and n-ZnO nanorod arrays directly. The design showed weak photovoltaic performance. However, the p-n heterojunction system shows the significantly enhanced photocurrent and photovoltage with the assistance of filling electrolyte (I3 − /I − ). The charge carrier dynamics indicates that the reversible redox couple (I3 − /I − ) electrolyte can promote electron transfer from CuO to ZnO better, i.e. better charge separation efficiency and photocurrent.